Intraconal orbital displacement of a dental implant treated with an endoscopically-assisted approach. Issue 4 (May 2020) - Bocchialini, G.; Negrini, S.; Bolzoni Villaret, A.; Pianta, L.
Abstract: Foreign bodies in the orbit are uncommon, and dental intraconal displacement is even more rare. We aim to present and discuss what is to our knowledge the first case and its management. A 55-year-old woman had a dental implant placed in the upper right maxilla, but during the procedure it was displaced into the orbit. It was removed reliably and safely through an enlarged endoscopic medial maxillectomy.